A Combined Effect of G-Quadruplex and Neuro-Inducers as an Alternative Approach to Human Glioblastoma Therapy - Pavlova, Galina; Kolesnikova, Varvara; Samoylenkova, Nadezhda; Drozd, Sergey; Revishchin, Alexander; Shamadykova, Dzhirgala; Usachev, Dmitry Y.; Kopylov, Alexey (Frontiers in Oncology, 2022)
Cancer cell reprogramming based on a treatment with G-quadruplex, having antiproliferative power, in combination with small molecules, able to develop iPSCs into neurons, could create a novel approach to diminish a chance for glioblastoma recurrence, as well as to circumvent a tumor resistance to a conventional therapy. In this research, we have tested several combinations of factors to affect both total cell cultures, derived from tumor tissue of patient after surgical resection, and two subfractions of this cell culture, after dividing into CD133-enriched and CD133-depleted populations (assuming CD133 to be a marker of glioblastoma stem-like cells). CD133+ and CD133– cells exhibit different responses to the combinations of factors: CD133+ cells having stem-like properties, and being more resistant. Therefore, an ability to affect CD133+ cells provides a possibility to circumvent resistance to a conventional therapy, as well as to build a promising strategy for translation to improve treatment of patients with glioblastoma.